The CGRP-RAMP1 signaling enhances anti-Aspergillus fumigatus immune response - Onah, Chinemerem (Kansas State University, 2023)
Aspergillus fumigatus is the single most common cause of fungal pneumonia and is listed as the World Health Organization’s fungal priority pathogen. Aspergillus fumigatus opportunistic infections are on the rise due to an increasing proportion of immunocompromised and chronic lung disease patients. These individuals are more likely to acquire Invasive Pulmonary Aspergillosis (IPA) and lethal pneumonia caused by A. fumigatus. IPA and fungal pneumonia lead to dysregulated inflammation, rapid destruction of airway barrier permeability, and immune dysfunction. Innate immune cells, macrophages, neutrophils, and monocytes are critical for rapid fungal clearance and host protection against A. fumigatus. The lungs are heavily innervated by nociceptive sensory neurons which help to maintain homeostasis and immune cell functions, and they also secrete the neuropeptide calcitonin gene-related peptide (CGRP) to mediate pain sensations. Although A. fumigatus-specific therapeutics exist, they fail to provide absolute treatment to IPA and come with huge clinical limitations. Therefore, this study aims to understand the crosstalk between lung-innervating nociceptive neurons and the innate immune system to identify novel anti-A. fumigatus therapeutic target(s) through the signaling of these two systems. To understand the role of CGRP signaling in anti-fungal innate immune response, we employed immunohistochemistry, intracellular conidia killing assay, and flow cytometry analyses. We found an increase in the level of phagocytosis and intracellular killing of conidia by Bone Marrow (BM)-derived Macrophages and BM monocytes in the presence of CGRP. Also, flow cytometry and total cellular ROS analyses indicate significant increases in phagocytosis and effector function within neutrophils in the presence of CGRP. These effects were abolished when immune cells that lack the RAMP1 (receptor for CGRP) were employed. Altogether, our findings support the notion that the CGRP-RAMP1 signaling increases anti-A. fumigatus innate immune response during A. fumigatus infection. This highlights the relevance of this interaction to A. fumigatus infections and points to it as a potential therapeutic option for the treatment/management of this infection. Further studies are required to understand the translation of these findings into in vivo and/or clinical settings.
Keywords: Aspergillus fumigatus; Immune response; RAMP1; Signaling; Aspergillosis; Calcitonin gene-related peptide CGRP